Chaperonopathies: Spotlight on Hereditary Motor Neuropathies - Lupo, Vincenzo; Aguado, Carmen; Knecht, Erwin; Espinós, Carmen (Frontiers in Molecular Biosciences, 2016)
Distal hereditary motor neuropathies (dHMN) are a group of rare hereditary neuromuscular disorders characterized by an atrophy that affects peroneal muscles in the absence of sensory symptoms. To date, 23 genes are thought to be responsible for dHMN, four of which encode chaperones: DNAJB2, which encodes a member of the HSP40/DNAJ co-chaperone family; and HSPB1, HSPB3, and HSPB8, encoding three members of the small heat shock protein family. While around 30 different mutations in HSPB1 have been identified, the remaining three genes are altered in many fewer cases. Indeed, a mutation of HSPB3 has only been described in one case, whereas a few cases have been reported carrying mutations in DNAJB2 and HSPB8, most of them caused by a founder c.352+1G>A mutation in DNAJB2 and by mutations affecting the K141 residue in the HSPB8 chaperone. Hence, their rare occurrence makes it difficult to understand the pathological mechanisms driven by such mutations in this neuropathy. Chaperones can assemble into multi-chaperone complexes that form an integrated chaperone network within the cell. Such complexes fulfill relevant roles in a variety of processes, such as the correct folding of newly synthesized proteins, in which chaperones escort them to precise cellular locations, and as a response to protein misfolding, which includes the degradation of proteins that fail to refold properly. Despite this range of functions, mutations in some of these chaperones lead to diseases with a similar clinical profile, suggesting common pathways. This review provides an overview of the genetics of those dHMNs that share a common disease mechanism and that are caused by mutations in four genes encoding chaperones: DNAJB2, HSPB1, HSPB3, and HSPB8.